Il modello toscano dell’ “accoglienza diffusa” dei richiedenti asilo. Quattro diverse esperienze nel territorio senese - Berti, Fabio; Nasi, Lorenzo; Valzania, Andrea (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
In the last years the micro-level and decentralisedaccoglienza diffusais the predo-minant approach to the ‘management’ of the asylum seekers and refugees adopted inthe Tuscany region (Italy). Using the approach of visual sociology, the paper showsthe main results of this “model” in four different sub-areas of province of Siena,investigates the difference between the local changing scenarios strictly linking dayby day strategies to structural factors.